Assessing the Viability of Converting Fuel-Based Pedicabs to Electric Pedicabs: A Case Study in Padang - Hidayat; Azriyenni Azhari Zakri; Iman Satria; Duskiardi; Arzul; Umair Ali (International Journal of Electrical, Energy and Power System Engineering)
This study evaluates the feasibility of converting oil-powered three-wheeled pedicabs to electric vehicles to support sustainable urban transportation. The research focuses on pedicabs in Padang, which are commonly adapted from motorcycles. The feasibility assessment includes technical, financial, and demand analysis to determine the viability of the conversion. A survey was conducted among pedicab users to assess operational costs, fuel consumption, maintenance expenses, awareness of green energy, and willingness to transition to electric-powered pedicabs. The technical design involved selecting conversion components, estimating costs, and analyzing post-conversion operational expenses. The proposed electric pedicab utilizes a 2 kW, 72 V BLDC motor, with an estimated conversion cost of IDR 10 million. The operational cost before conversion is IDR 150,000 per week. Financial analysis shows that while initial operating costs for electric pedicabs are higher, they become more economical after 103 weeks. The findings indicate that the conversion is technically and financially feasible, with 53.85% of surveyed pedicab users expressing willingness to switch to electric models. This study highlights the potential to reduce fossil fuel dependence and promote environmentally friendly transportation alternatives in urban areas.